Physical work environment factors affecting risk for disability pension due to mental or musculoskeletal diagnoses among nursing professionals, care assistants and other occupations: a prospective, population-based cohort study - Constanze Leineweber; Klas Gustafsson; Staffan Marklund; Gunnar Aronsson (BMJ Open)
Objective To study the influence of physical work factors on the risks of future disability pension (DP) due to mental or musculoskeletal diagnoses among nursing professionals, care assistants and all other occupations in the general working population in Sweden.Methods The prospective population study was based on representative samples of working individuals (n=79 004) aged 16–64, interviewed in the Swedish Work Environment Survey between 1993 and 2013. Information on diagnosed DP in 1994–2014 was gathered from the Social Insurance Agency’s database. The focus was on nursing professionals (registered nurses and midwives) and care assistants, for example, assistant nurses and hospital ward assistants. The outcome was DP, classified into two diagnostic groups. Associations between physical work factors and risk of DP were calculated using Cox regression with HR and 95% CI.Results Physical work factors were associated with future DP after adjusting for sociodemographic conditions and psychosocial work factors among care assistants (n=10 175) and among all other occupations (n=66 253), but not among nursing professionals (n=2576). The increased risk among care assistants (n=197) exposed to heavy physical work was 66% (HR 1.66, 95% CI 1.39 to 1.97), and for those exposed to strenuous work postures (n=420) it was 56% (HR 1.56, 95% CI 1.35 to 1.80). Physical work indicators were mainly associated with musculoskeletal DP diagnoses among care assistants, but two indicators were significant also for mental diagnoses. An increased risk of DP was found among nursing professionals (n=102) exposed to detergents or disinfectants (HR 1.48, 95% CI 1.06 to 2.05), but not among care assistants.Conclusions Heavy physical work and strenuous postures are predictors of future DP, particularly among care assistants and in the general working population. In order to reduce early exit from the workforce, efforts should be made to improve physical and ergonomic working conditions.